Formação continuada numa perspectiva da educação para a inteireza : uma necessidade do professor de creche - Meinicke, Dinorá (2017)
This study is about continuing education for daycare teachers. The research was developed from a qualitative research of hermeneutical approach and had as objective to understand how the Actions of Continuing Education offered to the Kindergarten Teacher, by the Municipal Secretary of Education - SME of Florianópolis / SC, in the period 2013-2015, instigated training in the perspective of an Education for Integrality. Theoretically the study is based on: Candau; Cunha; Gatti; Gatti e Barreto; Imbernón; Marin; Nóvoa; Kramer Galvani; Barbosa; Baumann; Campos; Freitas e Pelizon; Nóvoa; Pimenta; Catanante; Gallegos; Moraes; Naranjo; Olbrzymekm; Portal; Roselló; Yus; Wolman; Zohar e Marshall, among others. By definition, Education for Integrality is a proposal that implies and proposes to develop the constitutive dimensions of Being by instigating and inspiring the development of self-knowledge and self-formation. This is a transdisciplinary movement that seeks to understand the complementarity and synergy that surrounds and circulates among the constitutive dimensions of Being (social, emotional, spiritual and rational) in its process of Continuing Formation. The research had as subjects six servers that were at the forefront of planning and / or implementation of the focus actions of this study. Data collection was done through documentary research and semi-structured interviews, and data analysis was submitted to the principles of Discursive Textual Analysis. Three conceptions of Continuing Education were identified that supported the actions offered by SME of Florianópolis / SC in the formation of the Teacher of Early Childhood Education, which were improved over the period. It was verified that the actions were offered through meetings, conferences and a symposium. It was concluded that, in the period in which the training actions that comprise this study were thought of, they did not contemplate the constitutive dimensions of Being in their planning; However, it was observed that, although the Secretariat did not devise such actions for this purpose, the constitutive dimensions of Being permeated its development. The findings of this study indicate that the Municipal Secretary of Education of Florianópolis / SC recognizes the importance of enabling Continuing Education and is available to invest in studies and actions that contemplate the perspective of an Education for Integrality.